2021
DOI: 10.15237/gida.gd21032
|View full text |Cite
|
Sign up to set email alerts
|

BURUK, BURUK OLMAYAN ve YABANİ (ANAÇ) HURMALARIN TOPLAM FENOLİK BİLEŞEN, ANTİOKSİDANT KAPASİTE ve IN-VITRO SİMULE EDİLMİŞ BİYOALINABİLİRLİK ÖZELLİKLERİ

Abstract: Persimmon which is widely known as "Trabzon Hurması" and "Cennet Meyvesi" is a very popular fruit with bright orange color. In the presented study, extractable, non-extractable, total phenolic content (TPC), antioxidant capacity (AC) and bioaccessibility of Trabzon persimmons (astringent, non-astringent and wild persimmon) were determined. The results of this study indicated that all types of persimmons have great importance both on TPC, AC and bioaccessibility. Compared to astringent and non-astringent types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…In different varieties of pomegranate, phenolic compounds (ellagic acid, gallic acid, chlorogenic acid, caffeic acid, vanillic acid, ferulic acids trans-2-hydrocinnamic acid, quercetin) and flavonoids (catechin, rutin, quercetin and phloridzin) were identified (Hmid et al, 2017;Djenidi et al, 2020;Tekin and Kucukbay et al, 2020). Phytochemical analysis by Lee et al (2012), Murathan (2020) and Aydin (2021) reported the presence of tartaric acid, malic acid, lactic acid, gallic acid, citric acid, catechins, phenols, flavonoids and ascorbic acid in persimmon fruit. Radish fruits are rich in flavonoids (such as myricetin, catechin, epicatechin, and quercetin), phenols (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In different varieties of pomegranate, phenolic compounds (ellagic acid, gallic acid, chlorogenic acid, caffeic acid, vanillic acid, ferulic acids trans-2-hydrocinnamic acid, quercetin) and flavonoids (catechin, rutin, quercetin and phloridzin) were identified (Hmid et al, 2017;Djenidi et al, 2020;Tekin and Kucukbay et al, 2020). Phytochemical analysis by Lee et al (2012), Murathan (2020) and Aydin (2021) reported the presence of tartaric acid, malic acid, lactic acid, gallic acid, citric acid, catechins, phenols, flavonoids and ascorbic acid in persimmon fruit. Radish fruits are rich in flavonoids (such as myricetin, catechin, epicatechin, and quercetin), phenols (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative antioxidant analysis between astringent, nonastringent and wild types of persimmons by Aydin (2021) indicated that the wild type had higher antioxidant potential than the other types. The ABTS, CUPRAC, DPPH, and FRAP activities were 112.…”
Section: Resultsmentioning
confidence: 99%